The mucosal cellular response to infection with Ancylostoma ceylanicum - Alkazmi, L.M.M.; Dehlawi, M.S.; Behnke, J.M. (Cambridge University Press, 2008)
Although hookworms are known to stimulate inflammatory responses in the intestinal mucosa of their hosts, there is little quantitative data on this aspect of infection. Here we report the results of experiments conducted in hamsters infected with Ancylostoma ceylanicum. Infection resulted in a marked increase in goblet cells in the intestinal mucosa, which was dependent on the number of adult worms present and was sustained as long as worms persisted (over 63 days) but returned to baseline levels within 7 days of the removal of worms by treatment with ivermectin. Increased mast cell responses were also recorded. Levels were again dependent on the intensity of worm burdens and lasted as long as 63 days after infection. When worms were eliminated, mast cell numbers took over 2 weeks to return to normal. Paneth cell numbers fell soon after infection, the degree of reduction being dependent on the worm burden. After clearance of worms, Paneth cell numbers returned to normal within a week, but then rebounded and numbers rose to higher levels than those in control naıve animals. The time course of the response was similar whether animals experienced a chronic low-intensity infection without loss of worms or a higher intensity infection during the course of which worm burdens were gradually reduced. Clearly, A. ceylanicum was able to induce a marked inflammatory response in its host’s intestine which was sustained for over 9 weeks after infection, and which hamsters appeared able to tolerate well. Our data draw attention to the resilience of hookworms which, unlike many other nematodes, are able to survive for many weeks in a highly inflamed intestinal tract.